Effect Of Minimum Wage and Number Of Hotels On Labour Absorption In Dumai City In 2012-2023 - Simanjuntak, Fransa Juve Jonatan; Widayatsari, Any; Zamaya, Yelly (Dinasti International Journal of Economics, Finance & Accounting, 2025)
An increase in the tourism sector can increase income and employment in Dumai City. This A study was carried out to test and analyse the impact of the number of hotels and the minimum wage on employment in the city of Dumai in 2012-2023. This research was conducted in Dumai City, Riau Province with the tourism sector as the object of research. The research uses secondary data with a quantitative approach. Data from the Central Bureau of Statistics and the Dumai City Labour Bureau. Data analysis using SPSS software. The results of the study can be said that partially the number of hotels has no effect on employment while the minimum wage has a positive and significant effect on employment in Dumai City.